Running economy and effort after cycling: Effect of methodological choices - du Plessis, C.; Blazevich, A. J.; Abbiss, C.; Cochrane Wilkie, J. (Journal of Sports Sciences, 2020)
Prior exercise can negatively affect movement economy of a subsequent task. However, the impact of cycling exercise on the energy cost of subsequent running is difficult to ascertain, possibly because of the use of different methods of calculating economy. We examined the influence of a simulated cycling bout on running physiological cost (running economy, heart rate and ventilation rates) and perceptual responses (ratings of perceived exertion and effort) by comparing two running bouts, performed before and after cycling using different running economy calculation methods. Seventeen competitive male triathletes ran at race pace before and after a simulated Olympic-distance cycling bout. Running economy was calculated as V.O2 (mL/kg·min), oxygen cost (EO2, mL/kg·min) and aerobic energy cost (Eaer, J/kg·m). All measures of running economy and perceptual responses indicated significant alterations imposed by prior cycling. Despite a good level of agreement with minimal bias between calculation methods, differences (p < 0.05) were observed between Eaer and both V.O2 and EO2. The results confirmed that prior cycling increased physiological cost and perceptual responses in a subsequent running bout. It is recommended that Eaer be calculated as a more valid measure of running economy alongside perceptual responses to assist in the identification of individual responses in running economy following cycling.